KRISIS TENAGA KESEHATAN TERHADAP MANAJEMEN SUMBER DAYA MANUSIA DI MASA PANDEMI COVID-19 - Nur Khamimah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This crisis in health workers has affected the national health system, but there is little research on how these HR issues affect medical workers. Understanding the impact on the health conditions of medical personnel is very important in the midst of the COVID-19 outbreak that is still sweeping the world. With the empirical literature, we have succeeded in summarizing the impact of the HR crisis on the health of medical personnel. This study confirms that the human resource crisis is transmitted to medical personnel through several models: (1) decreasing the quality of health services; (2) the impact of inadequate service measures; and (3) increasing demand for health services from patients; (4) A wave of public protests for treatment; (5) service and budget inefficiency.